Alteration of Blood Parameters in Non-Dialyzed Patients of Chronic Kidney Disease - Najat Mohammed,; Tahani Mohammed,; Nisreen Farag, (AlQalam Journal of Medical and Applied Sciences, 2025)
Chronic kidney disease (CKD) is a serious health problem that can lead to end-stage renal disease. Patients with CKD are usually suffered from anemia, which is one of the major consequences of kidney damage which in turn lead to reduce quality of life, increased risk of cardiovascular disease and cognitive impairment. The study aimed to assess the hematological abnormalities in the CKD patients during pre-dialyzed conditions in EL-Beyda City. The study was included 107 patients who are attended to Nephrology Department in EL-Bayda Medical Center in the period from November 2021 to March 2022. The study was included all CKD stages and were not on dialysis and they were following upped by these centers regularly each month. Data sources were obtained from the personal interview with patients and the records files in Nephrology units. Blood samples were taken in EDTA tube to measure complete blood counts (CBC) include hemoglobin (Hb), hematocrit (HCT), Mean cell volume (MCV), Mean cell hemoglobin (MCH), Mean cell hemoglobin concentration (MCHC), white blood cells (WBC) and platelets count (PLT), as well as renal function tests (blood urea and creatinine). The data were analyzed by Minitab version17. Out of 107 patients were included in this study, 63(58.8%) of patients were females and 44(41.1%) were males, The majority of patients had chronic diseases which could be the contributing cause of CKD; 62% were suffered from hypertension, 40% suffered from diabetes. Anemia was the main abnormality in our study which observed in 49 of participants (45.8%) while the others were non anemic accounting 54% (14.6±0.23). There was a significant difference in the mean of hemoglobin and hematocrit between anemic and non-anemic participants (p- value=0.000). Red cell indices showed normocytic normochromic anemia, thrombocytopenia was noticed in 7 (14%) of patients and leukocytosis was reported in 9 (18%) of them. We can conclude that developing of anemia in CKD patients is associated with poor outcomes and requires a careful management to avoid comorbidities. مرض الكلى المزمن هو مشكلة صحية خطيرة يمكن أن تؤدي إلى مرض الكلى في مرحلته النهائية. يعاني مرضى الفشل الكلوي المزمن عادة من فقر الدم، وهو أحد العواقب الرئيسية لتلف الكلى مما يؤدي بدوره إلى انخفاض جودة الحياة وزيادة خطر الإصابة بأمراض القلب والأوعية الدموية وضعف الإدراك. هدفت الدراسة إلى تقييم التشوهات الدموية لدى مرضى الفشل الكلوي المزمن أثناء ظروف ما قبل الغسيل الكلوي في مدينة البيضاء. شملت الدراسة 107 مريضًا يراجعون قسم أمراض الكلى في مركز البيضاء الطبي في الفترة من نوفمبر 2021 إلى مارس 2022. شملت الدراسة جميع مراحل الفشل الكلوي المزمن ولم يكونوا على غسيل الكلى وكانوا يتابعون من قبل هذه المراكز بانتظام كل شهر. تم الحصول على مصادر البيانات من المقابلة الشخصية مع المرضى وملفات السجلات في وحدات أمراض الكلى. تم أخذ عينات الدم في أنبوب EDTA لقياس تعداد الدم الكامل بما في ذلك الهيموجلوبين والهيماتوكريت ومتوسط ​​حجم الخلايا ومتوسط ​​الهيموجلوبين الخلوي ومتوسط ​​تركيز الهيموجلوبين الخلوي وخلايا الدم البيضاء وعدد الصفائح الدموية بالإضافة إلى اختبارات وظائف الكلى (اليوريا في الدم والكرياتينين). تم تحليل البيانات بواسطة Minitab version17. من بين 107 مريض تم تضمينهم في هذه الدراسة، كان 63 (58.8٪) من المرضى من الإناث و 44 (41.1٪) من الذكور، وكان لدى غالبية المرضى أمراض مزمنة يمكن أن تكون السبب المساهم في مرض الكلى المزمن؛ حيث عانى 62٪ من ارتفاع ضغط الدم، و 40٪ يعانون من مرض السكري. كان فقر الدم هو الشذوذ الرئيسي في دراستنا والذي لوحظ في 49 من المشاركين (45.8٪) بينما كان الآخرون غير مصابين بفقر الدم بنسبة 54٪ (14.6 ± 0.23). كان هناك فرق كبير في متوسط ​​الهيموجلوبين والهيماتوكريت بين المشاركين المصابين بفقر الدم وغير المصابين به (قيمة الاحتمالية = 0.000). أظهرت مؤشرات خلايا الدم الحمراء فقر دم طبيعي كرومي، ولوحظ نقص الصفيحات الدموية في 7 (14٪) من المرضى وتم الإبلاغ عن زيادة عدد الكريات البيضاء في 9 (18٪) منهم. يمكننا أن نستنتج أن تطور فقر الدم لدى مرضى الفشل الكلوي المزمن يرتبط بنتائج سيئة ويتطلب إدارة دقيقة لتجنب الأمراض المصاحبة